EPS dan NPM terhadap Harga Saham - Robbi Wildan Fitra; Nursito Nursito (Journal of Management and Bussines (JOMB), 2022)
This research aims to know the Effect Of Earning Per Share (EPS) and Net Profit Margin (NPM) partially or simultaneously on Price Stock ini Pulp and Paper Manufacturing Companies Listed on Indonesian Stock Exchange for the 2015-2018. The technique used to determined sample is purposive sampling and obtained 7 companies for 3 years of research. The research method used is descriptive verificative with Multiple Linear Regression Analysis. The result showed that EPS and NPM Partially had a significant effect on Stock Price. Simultaneously EPS and NPM influence Price Stock. In conclusion, Earning Per Share (EPS) and Net Profit Margin (NPM) partially and simultaneously affect the share price of manufacturing companies in the pulp and paper sub-sector. Keywords: Earning Per Share (EPS), Price Stock, Net Profit Margin (NPM)